COVID-19 and children who experience special educational needs: Caregivers’ experiences, coping strategies, and support needs - Fernandes, Jenna (University of the Witwatersrand, Johannesburg, 2023)
Every aspect of parenting becomes magnified when caring for a child who experiences special educational needs, especially during a pandemic. Despite the wide recognition that the pandemic intensified existing stressors for caregivers of children who experience special educational needs as indicated by reports of significant declines in mental health, there is a scarcity of research exploring caregivers’ experiences during the pandemic, and especially within the South African context. Therefore, the aim of this study was to explore the experiences of South African caregivers, their available support structures, coping strategies, and support needs. An exploratory qualitative research design was employed, in which twelve caregivers of children who experience special educational needs participated in semi structured interviews. Reflexive thematic analysis was used to analyse the data, and subsequently, the researcher developed five intersecting themes and fourteen subthemes. Notably, the five themes were, “exhausted to the bone”, twice as isolated, finding the light in the dark, soldiering on and learning to cope, and a wish for change and advocacy. Critically, the results of the research study suggest that despite the difficulties experienced by caregivers, there were opportunities for growth and development. However, there is a deep desire for there to be more understanding and tolerance of differences.
A research report submitted in partial fulfilment of the requirements for the degree of Masters in Education (Educational Psychology) to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023
Keywords: Caregivers’ Experiences; Coping Strategies; COVID-19 Pandemic; Reflexive Thematic Analysis; Special Educational Needs; Support Needs; UCTD; SDG-4: Quality education